Menggali Perkembangan Metode Tafsir dari Zaman Rasulullah hingga Era Modern - Hayatuddin, Muhammad Ihsan; Hakim, Lukman Nul (Indonesian Journal Publisher, 2024)
The development of methods for interpreting the Quran has evolved from the time of Prophet Muhammad SAW to the present modern era. During the time of the Prophet, the interpretation of the Quran was carried out directly by him and his companions with a relatively straightforward understanding. However, as time passed, the methods of interpretation underwent significant developments. Initially, the interpretation of the Quran was done directly from oral sources and was not well-documented. However, after the Prophet's passing, the companions began to develop more systematic methods of interpreting the Quran. They utilized the direct understanding from the Prophet as well as the social and cultural context of that time. Subsequently, during the era of the Tabi'in (the generation after the companions), the methods of interpretation continued to evolve with more detailed explanations and interpretations. The Tabi'in scholars sought to elaborate on the meanings and messages of the Quran in greater detail, both in linguistic and historical contexts. The development of interpretation methods continued in the following periods. In the contemporary and modern era, many interpretation books have been compiled by contemporary scholars. The methods of interpretation used encompass linguistic, historical, contextual, and philosophical approaches to the Quran. Modern scholars combine scientific knowledge and methodologies with traditional understanding to better comprehend the Quran.